Suluk Linglung: Sufi Aphorism of Sunan Kalijaga - Latifah, Kunfuaidah; Rahmawati, Lady Eka (Sutasoma : Jurnal Sastra Jawa, 2025)
Suluk Linglung Sunan Kalijaga is a literary work not widely known to the general public. This Suluk reflects Sunan Kalijaga’s comprehensive religious experience; it is his aphorism in expressing thoughts and ideas. Suluk Linglung tells of Sunan Kalijaga’s anxiety regarding spiritual journeys. The research method applies a hermeneutic approach with the help of philological theory. The primary data source is Suluk Linglung's text, which was translated by Kasri in 1993. The data collection technique uses literature study, while data analysis involves the stages of identification, clarification, hermeneutic, and contextual analysis. The study results found that Suluk Linglung emphasizes the science of nature more. Suluk Linglung places more emphasis on the science of nature. Its principles are based on the stage (maqam) in the Sufi tradition, which ends with the Insan Kamil phase. The first stage is the “preparation” phase, emphasizing the dimensions of consciousness within humans. The second stage, the process phase from exoteric to esoteric, is an effort to search for the essential sciences. In the third stage, the journey to Al Khalq, to achieve the science of hidayat, he met the Prophet Khidzir (inner teacher), who taught the science of hidayat. The fourth stage is Insan Kamil, where he has gained faith. Hidayat reached the tajalli phase. Search for the essential sciences. The third stage, the journey to truth, or from being to al-Khalq, is an effort to achieve the Science of Hidayat. He met the Prophet Khidzir (inner teacher), who taught the science of Hidayat. The fourth stage is Insan Kamil, where he has gained Faith in this phase. Hidayat reached the Tajalli phase.